2001
DOI: 10.1093/ndt/16.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of renal replacement therapy in the very elderly

Abstract: Very elderly ESRD patients on RRT have a very poor outcome and, since they are the largest growing group of RRT patients, this has important implications for future health policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
70
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 18 publications
13
70
1
Order By: Relevance
“…It is however of interest that-in agreement with the general population-elderly dialysis patients were more likely to have high Center of Epidemiologic Studies Depression Rating Scale scores in Europe and in Japan, indicating the higher likelihood of possible clinical depression among elderly hemodialysis patients. As expected, mortality rates were higher in elderly hemodialysis patients (28). Median survival for patients aged Ն75, 45 to 74, and Ͻ45 years was 3, 6, and 12 years, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…It is however of interest that-in agreement with the general population-elderly dialysis patients were more likely to have high Center of Epidemiologic Studies Depression Rating Scale scores in Europe and in Japan, indicating the higher likelihood of possible clinical depression among elderly hemodialysis patients. As expected, mortality rates were higher in elderly hemodialysis patients (28). Median survival for patients aged Ն75, 45 to 74, and Ͻ45 years was 3, 6, and 12 years, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…It has been reported that the 1-year survival of those patients .75 years old on HD is 53.5%, whereas at 5 years, it is as low as 2.4%. 16,17 Overall, our data suggest that fistula first is not the clearly superior strategy in the elderly population, particularly for octogenarians and nonagenarians. However, our data support the notion that placing a catheter first does seem to be the 19,20 Using this time to plan and create a fistula or graft seems prudent.…”
Section: Discussionmentioning
confidence: 77%
“…This is surprising, in light of the fact that ESRD patients have a high annual mortality rate (1). Moreover, hospitalizations and complications are common, and many patients have some degree of cognitive impairment (3,20,21). For all of these reasons, advance directives are likely to be particularly useful in this population.…”
Section: Discussionmentioning
confidence: 99%